Increased [CO2] causes changes in physiological and genetic responses in C4 crops: A brief review - da Silva, Renan Gonçalves [UNESP]; Alves, Rita de Cássia; Zingaretti, Sonia Marli [UNESP] (MDPI, 2020)
Climate change not only worries government representatives and organizations, but also attracts the attention of the scientific community in different contexts. In agriculture specifically, the cultivation and productivity of crops such as sugarcane, maize, and sorghum are influenced by several environmental factors. The effects of high atmospheric concentration of carbon dioxide ([CO2]) have been the subject of research investigating the growth and development of C4 plants. Therefore, this brief review presents some of the physiological and genetic changes in economically important C4 plants following exposure periods of increased [CO2] levels. In the short term, with high [CO2], C4 plants change photosynthetic metabolism and carbohydrate production. The photosynthetic apparatus is initially improved, and some responses, such as stomatal conductance and transpiration rate, are normally maintained throughout the exposure. Protein-encoding genes related to photosynthesis, such as the enzyme phosphoenolpyruvate carboxylase, to sucrose accumulation and to biomass growth and are differentially regulated by [CO2] increase and can variably participate owing to the C4 species and/or other internal and external factors interfering in plant development. Despite the consensus among some studies, mainly on physiological changes, further studies are still necessary to identify the molecular mechanisms modulated under this condition. In addition, considering future scenarios, the combined effects of high environmental and [CO2] stresses need to be investigated so that the responses of maize, sugarcane, and sorghum are better understood.
Keywords: C4 plants; CO2 enrichment; Gene expression; Photosynthesis; Productivity